Examining the Impact of Principals’ Leadership on Teachers’ Organizational Commitment: A Meta-Analysis - Furtasan Ali Yusuf (Journal of Educational Studies, 2026)
This study analyzes the relationship between principals’ leadership and teachers’ organizational commitment using a meta-analysis of studies from 2017–2025, addressing concerns about burnout and inconsistent prior findings. It aims to evaluate result variations, determine the overall effect size, and examine potential publication bias. This study employed a quantitative meta-analytic design by synthesizing 30 eligible journal articles. The included studies were drawn from formal educational settings and represented several leadership categories, including transformational-based, instructional/strategic, ethical-relational, and distributed/participative leadership. Correlation coefficients were used as the main effect size indicator, while reported t-values were converted into correlation coefficients when necessary. The eligibility criteria included studies that examined the relationship between principals’ leadership and teachers’ organizational commitment, reported statistical data (e.g., r or t values), were conducted in formal educational settings, published in indexed journals, provided clear sample sizes, were published between 2017 and 2025, and written in English. The studies were systematically identified through searches in several academic databases, including Scopus, Web of Science, ERIC, EBSCO and ScienceDirect. The data were analyzed using a correlation-based meta-analysis with a random-effects model in JASP to test heterogeneity, estimate the combined effect size, and examine publication bias. The findings showed that the meta-analysis included 30 studies examining the relationship between principals’ leadership and teachers’ organizational commitment. The results indicated very high heterogeneity across studies (I² ranging from 97.84% to 99.60%). Overall, principals’ leadership was positively and significantly related to teachers’ organizational commitment, with instructional/strategic leadership demonstrating the strongest pooled effect size (r = 0.61, 95% CI [0.34, 0.79]). The publication bias analysis further indicated that the meta-analytic findings were statistically robust. The study concludes that principals’ leadership is an important factor in strengthening teachers’ organizational commitment, although the magnitude of its effect varies across leadership approaches and educational contexts.